2018
DOI: 10.1111/bcpt.13024
|View full text |Cite
|
Sign up to set email alerts
|

Use of Non‐Vitamin K Antagonist Oral Anticoagulants 2008–2016: A Danish Nationwide Cohort Study

Abstract: We aimed to provide detailed utilization data on the total use of non-vitamin K antagonist oral anticoagulants (NOACs) since their introduction in 2008. Using the nationwide Danish National Prescription Registry, we identified all individuals filling prescriptions for NOACs 2008-2016. We reported the development in incident and prevalent users and explored baseline characteristics and treatment persistence according to treatment indication. A total of 126,691 NOAC users were identified within the Danish popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
2
31
1
2
Order By: Relevance
“…Although these drugs had a later market entry than dabigatran and rivaroxaban, the use of especially apixaban among AF patients is extensive. 6,46,47 Further, in a recent registerbased drug utilization study, we showed that 16% of all AF patients initiating apixaban during the period of June 2016 to June 2017 in Denmark switched directly from VKA. 48 In the VKA-experienced stratum of the ARISTOTLE (Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation) trial, the risks of ischaemic stroke, major bleeding and intracranial bleeding were significantly lower in the apixaban arm than in the warfarin arm.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although these drugs had a later market entry than dabigatran and rivaroxaban, the use of especially apixaban among AF patients is extensive. 6,46,47 Further, in a recent registerbased drug utilization study, we showed that 16% of all AF patients initiating apixaban during the period of June 2016 to June 2017 in Denmark switched directly from VKA. 48 In the VKA-experienced stratum of the ARISTOTLE (Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation) trial, the risks of ischaemic stroke, major bleeding and intracranial bleeding were significantly lower in the apixaban arm than in the warfarin arm.…”
Section: Discussionmentioning
confidence: 85%
“…As DOACs also provide a more convenient therapy, their use has rapidly increased in AF patients. 5,6 A substantial proportion of AF patients initiating DOAC therapy are previous VKA users and thereby not naïve to oral anticoagulant therapy. 7 The majority of these 'VKA-experienced' DOAC users are ongoing VKA users switching to DOAC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Recently, we published a descriptive drug utilization study in Basic & Clinical Pharmacology & Toxicology on the use of direct oral anticoagulants (DOAC) in Denmark during 2008-2016. 1 A surprising finding was the large proportion of DOAC initiators in whom we were not able to identify a likely treatment indication using "the conventional approach", that is through hospital-based health registers. More specifically, among 126,691 Danish DOAC initiators, a total of 35 200 (28%) could not be classified with a major treatment indication, that is atrial fibrillation (AF), venous thromboembolism (VTE) or VTE prophylaxis following arthroplastic knee or hip surgery.…”
Section: Cohort Selection In Register-based Studies Of Direct Oral Anmentioning
confidence: 94%
“…Although DOAC use initiated in primary care seems most likely to be due to AF (since acute VTE patients are handled in the hospital setting), non-registered AF is unlikely to be the only reason for missing treatment indication proxies, as discussed in the primary paper. 1 As such, the underlying assumption that DOAC users with no registered treatment indication have AF may not be correct, and this approach may therefore introduce misclassification bias.…”
Section: Cohort Selection In Register-based Studies Of Direct Oral Anmentioning
confidence: 99%
“…Fewer drug‐drug interactions and fixed daily doses have made NOACs easy to prescribe and monitor. Without going into the details of their merits and demerits, there is evidence of an increasing shift to the clinical use of these expensive NOACs . Therefore, in advanced economies which can support the cost of NOACs, pharmacogenetics of warfarin may well become of academic interest only.…”
Section: What Is New and Conclusionmentioning
confidence: 99%